A method to quantify and visualize femoral head intraosseous arteries by micro‐CT. Issue 2 (14th April 2016) - Qiu, Xing; Shi, Xiaotian; Ouyang, Jun; Xu, Dachuan; Zhao, Dewei
Abstract: We describe a technique for perfusing a barium sulphate suspension into the intraosseous artery. Following the perfusion of abarium sulphate suspension into 14 fresh lower limbs of Chinese cadavers, micro‐CT scanning was applied to digitize, quantify and visualize the intraosseous arteries in the human femoral heads. Then, the femoral heads were removed and subjected to micro‐CT scanning. The data were imported into theamira andmimics programs to reconstruct and quantify the intraosseous arteries. The femoral head intraosseous artery lengths, areas, volumes, and femoral head bone volumes were quantified. The artery densities and artery ratios were calculated and analysed with independent‐samples t ‐tests. The intraosseous vasculature volume renderings were displayed as screenshots and videos made withamira . Many intraosseous artery study technologies were compared. The barium sulphate suspension was milky white in colour. The perfusion of the barium sulphate suspension followed by micro‐CT scanning provided a good representation of the intraosseous artery. The femoral head intraosseous artery lengths, areas and volumes, and the femoral head bone volumes were displayed as the X ¯ ± S . No differences were observed between the left and right femoral head intraosseous arteries in terms of the artery densities or artery ratios. The volume renderings and 3‐D orthogonal projections displayed the overall distributions of the intraosseous arteries. The videos clearly demonstrated the entry sites of the nutrition‐carrying arteries, their courses and branches, and the intraosseous arterial anastomoses. Our technique is the simplest and least time‐consuming method of producing accurate vascular three‐dimensional reconstructions. The perfusion of a barium sulphate suspension into intraosseous arteries combined with micro‐CT scanning can deliver high‐resolution 3‐D digitized data and images of intraosseous arteries. This technique does not require bone decalcification or bone dissection and thus significantly shortens the time required to quantify and display intraosseous arteries. This method provides a simple and rapid technique for quantifying and visualizing human intraosseous arteries.